Public service happiness and morale in the context of development: the case of Bhutan - Tshiteem, Karma; Everest-Phillips, Max (2016)
This article comprises the first detailed study published on the attitudes of civil servants in Bhutan. From the data collected under the 2015 gross national happiness (GNH) survey, an index of public service happiness (PSH) emerges, highlighting changes since 2010, with significant differences in happiness between female and male bureaucrats, and also between officials working in rural and urban areas. The findings highlight the importance of measuring public service morale. This topic that has been neglected over the last 25 years, in favour of public service motivation (PSM), due to a Western cultural bias for prioritising individual productivity over collective effectiveness. Attention to bureaucratic morale as measured by a PSH index could offer a a more appropriate approach to public service performance in non-Western settings. - Reproduced.
Keywords: Motivation - Bhutan; Civil service - Bhutan; Civil service